Asuhan Kebidanan Pada Ibu Hamil Trimester II Dengan Hipertensi Gestasional Di PMB Helni Ramzah, S.Tr.Keb Wilayah Kerja Puskesmas Sibiruang Koto Kampar Hulu Tahun 2023 - Mahera, Rifka; Mayasari, Endang (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Hypertension in pregnancy is one of the most important problems faced by public health because hypertension in pregnancy is a major cause of maternal and fetal morbidity and mortality. This study aims to determine midwifery care for pregnant women in the second trimester with gestational hypertension at PMB Helni Ramzah S.Tr.Keb in the Sibiruang Koto Kampar Hulu Community Health Center Work Area in 2023. The type of research used in the case study is descriptive research. The subject of this case study is a pregnant woman with gestational hypertension. The results of this research showed that midwifery care for pregnant women was provided by Ny. R, 24 years old, G1P0A0 experienced good changes from day to day, at the first visit the mother felt headache accompanied by nausea, pain scale 4, the pregnant woman's blood pressure was high, namely TD 140/93 mmHg. At the second visit the mother still felt headache accompanied by nausea, pain scale 3, blood pressure was still high, namely TD 140/90 mmHg. On the third visit, the mother stated that the headache had begun to decrease to the shoulders and nausea (+), appetite had begun to improve, the pain scale had dropped to 3 and blood pressure was still high at 138/90 mmHg. On the fourth visit, the mother felt that the headache and nausea had decreased, the pain scale had decreased to 2 and the blood pressure had also decreased or returned to normal to 135/80 mmHg. Pregnant women are expected to consume foods low in salt to keep blood pressure under control and avoid gestational hypertension.